[Image 38] - Smith, Captain Sir William [?ob. 1732] (My University, 1806)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
Favourite view of the Old Green Castle at Lough Foyle as seen from the site of the New fortifications there looking the way of the mountains towards Buncrana drawn by Captain Sir Wm Smith then Com. [indecipherable] Engineer 1806.
Keywords: Buncrana; Greencastle; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Lough Foyle (Northern Ireland and Ireland); Landscapes (Representations) 1800-1810